(untitled) (Revista Innova Educación, 2022)
Identifying the factors that influence the planning and subsequent development of a class at the university level is necessary for the development of critical thinking in higher education students. The objective of this article was to present the results of the interweaving of teaching experiences in the framework of a class in which the same pedagogical tools were used. The methodology used was a qualitative and ethnographic two-level strategy to identify the factors that influence the expected result at the time of planning a class. As a result, cohesion and satisfaction were, in general terms, achieved by both teachers, but not personalization, due to the structured style of one and the functional style of the other. It was concluded that the effectiveness of planning for meaningful learning and the development of critical thinking must consider, among other circumstances, the university classroom climate and the teaching style.